Implementation of Reading Method Using Letter Puzzles to Increase Interest in Learning to Read in Students at RA Ar Rohmah Suren - Hotimah; Karlina, Herlin (Jurnal Profesi Guru Indonesia, 2025)
Reading is important in children's development. This ability is very necessary for children's readiness to reach the next level of education. However, this is often a benchmark for parents to make their children good at reading even though the child is not ready to accept it. Based on the limitations of the problem that the researcher has stated above, the existing problem can be formulated as "How is the process of improving reading skills through the letter puzzle game method in Group B RA Ar Rohmah Dusun Lombung Suren Village, Ledokombo District which aims to improve reading skills through letter puzzle games in Group B RA Ar Rohmah Dusun Lombung Suren Village, Ledokombo District. The method used is in accordance with that carried out by the researcher, so the results of this study are that the average early reading skills of children get an average of "Good". This is evidenced by the increase that occurs at each meeting held. In cycle I, meetings 1-3 obtained an average overall score of 3.6 with the criteria of "Good" and achieved learning completeness of 72%. and achieved learning completeness of 90%. So it can be seen that the results of the study to improve early reading skills through the method of playing with word puzzle media successfully achieved 75% learning completion and increased optimally. The study was conducted with a classroom action research procedure, which went through four stages. The researcher carried out the stages one by one, namely planning, implementation, observation and reflection to obtain the desired data results in accordance with the learning completion criteria. However, in this study the increase produced was a quantitative increase while qualitatively obtained consistent results. Based on the description of the research results above, it can be concluded that the shortcomings that occurred in cycle I can be overcome through reflection carried out by the teacher, so that in cycle II there was an increase in both the process and the results of learning children's early reading skills.